NEW QUADRATIC-EXPONENTIAL DISTRIBUTION (Journal of Pharmaceutical Negative Results, 2022)
The proposed distribution is, a single parameter continuous probability distribution and has been introduced for statistical modeling of survival time data, a new form of Modified Mishra distribution with better results. It is named as ‘New Quadratic-Exponential Distribution (NQED). All the required characteristics such as probability mass function, cumulative probability distribution, probability generating function and mode of NQED have been obtained. Moments about the mean and about origin have been discussed. The Hazard rate function, Reliability function and the mean residual life function of NQED have been discussed. The estimation of parameters has been discussed by the method of moments as well as the maximum likelihood method. Goodness of fit has been applied to some data-sets to test validity of the proposed distribution. The main objective to introduce the proposed distribution is to give a better alternative of Lindley distribution (LD), Mishra distribution (MD), Quadratic-Exponential distribution (QED) and Modified Mishra distribution (MMD) for statistical modeling of over-dispersed survival time data.